Tráfico de menores em Portugal - Miranda, Diana Catarina Ribeiro (2017)
Child trafficking hasn’t always been known to the extent it holds today. Throughout history, the need to legislate particularly on the matter of child trafficking became real. However, due to the absence of specific laws, it was incorporated into two other crimes: human trafficking – on the international scene – and the prostitution of children – on the national scene. Not only after the 2007’s penal code reform, did the legislator regulate the crime of child trafficking. Internationally, there were created several legal instruments such as the Convention on the Rights of the Child and the Protocol to Prevent, Suppress and Punish Trafficking in Persons, especially Women and Children. These instruments reflected upon the Portuguese’s legal system, as well as the Spanish’s and the Italian’s, and forced the member States to legislate accordingly. Alongside with the new legislation it became necessary to differentiate the crime of child trafficking from other similar crimes, such as aiding illegal immigration. Today, the fight against child trafficking follows a procedure with extraordinary characteristics, for it is committed by highly organized criminals. It begins with the identification of the victim and comes to an end with the sentencing of the perpetrators. Currently, the refugee crisis is one of the greatest concerns of the international community. Not only are refugees arriving in the European borders in great numbers, but it is also believed that the trafficking organizations are operating on the refugees themselves. Therefore, the main goal of this dissertation is to analyze the characteristics of both national and international laws and regulations on child trafficking.